Legal Protection of Muzakki in Zakat Crowdfunding: Analysis of Maqasid Asy-Syari'ah - Mohammad Farid Fad; Ali Imron (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2021)
Abstract: The concept of crowdfunding is rooted in the concept of crowdsourcing. It utilizes a